Fluid interaction study: Hydrodynamic robot (FISHR) — Expansion of bioinspired soft robotic fish - Montana Ligman; Kioumars A. Rezaie; Ramya Shah; Chris Keeter; Bryson Sutterfield; Mirjam Fürth (HardwareX)
We introduce an enhanced iteration of OpenFish, a previously developed open-source soft robotic fish. The original model, developed at Delft University of Technology, successfully emulated thunniform swimming through a unique propulsion system utilizing both active and passive tail segments. This design aimed to optimize speed and efficiency while fostering future advancements in soft robotic fish research. To further enhance OpenFish, we undertook a redesign process, making modifications to the fish hull and internal components. These changes aimed to simplify construction, address waterproofing issues, and facilitate the development of an autonomous version of the fish. Our work encompasses an updated description of the construction process, customization options, and detailed insights into hardware implementation, including waterproofing techniques for the soft robotic fish.